Periodontitis in Chédiak-Higashi Syndrome: An Altered Immunoinflammatory Response. (January 2018) - Thumbigere Math, V.; Rebouças, P.; Giovani, P.A.; Puppin-Rontani, R.M.; Casarin, R.; Martins, L.; Wang, L.; Krzewski, K.; Introne, W.J.; Somerman, M.J.; Nociti, F.H.; Kantovitz, K.R.
Chédiak-Higashi syndrome (CHS), a rare autosomal recessive disorder caused by mutations in the lysosomal trafficking regulator gene (LYST), is associated with aggressive periodontitis. It is suggested that LYST mutations affect the toll-like receptor (TLR)–mediated immunoinflammatory response, leading to frequent infections. This study sought to determine the periodontal status of patients with classic (severe) and atypical (milder) forms of CHS and the immunoregulatory functions of gingival fibroblasts in CHS patients. In contrast to aged-matched healthy controls, atypical (n = 4) and classic (n = 3) CHS patients presented with mild chronic periodontitis with no evidence of gingival ulceration, severe tooth mobility, or premature exfoliation of teeth. As a standard of care, all classic CHS patients had undergone bone marrow transplantation (BMT). Primary gingival fibroblasts obtained from atypical and BMT classic CHS patients displayed higher protein expression of TLR-2 (1.81-fold and 1.56-fold, respectively) and decreased expression of TLR-4 (−2.5-fold and −3.85-fold, respectively) at baseline when compared with healthy control gingival fibroblasts. When challenged with whole bacterial extract of Fusobacterium nucleatum, both atypical and classic CHS gingival fibroblasts failed to up-regulate TLR-2 and TLR-4 expression when compared with their respective untreated groups and control cells. Cytokine multiplex analysis following F. nucleatum challenge showed that atypical CHS gingival fibroblasts featured significantly increased cytokine expression (interleukin [IL]–2, IL-4, IL-5, IL-6, IL-10, IL-12, interferon-γ, tumor necrosis factor–α), whereas classic CHS cells featured similar/decreased cytokine expression when compared with treated control cells. Collectively, these results suggest that LYST mutations in CHS patients affect TLR-2 and TLR-4 expression/function, leading to dysregulated immunoinflammatory response, which in turn may influence the periodontal phenotype noted in CHS patients. Furthermore, our results suggest that atypical CHS patients and classic CHS patients who undergo BMT early in life are less susceptible to aggressive periodontitis and that hematopoietic cells play a critical role in mitigating the risk of aggressive periodontitis in CHS. Knowledge Transfer Statement: Results from this study can be used to create awareness among clinicians and researchers that not all CHS patients exhibit historically reported aggressive periodontitis, especially if they have atypical CHS disease or have received bone marrow transplantation. LYST mutations in CHS patients may affect TLR-2 and TLR-4 expression/function leading to dysregulated immunoinflammatory response, which in turn may influence the periodontal phenotype noted in CHS patients.